Social Life: A Recent Studyon Lodhas of Mayurbhanj in Odisha, East India - Mohapatra, Ratnakar; Shirko Lambebo, Abesha (International Journal of Psychosocial Rehabilitation, 2020)
The social life of Lodhas stands separate from all other tribal groups of Odisha State in Eastern India. Mayurbhanj is one of the important tribal districts of the state of Odisha. The state of Odisha is regarded as the homeland of a number of different tribes, which have been considered as Scheduled Tribe numbering sixty two. Each tribe has its specific identity and unique character in the form of social organization, culture and language. The spoken language of each tribe is distinct and different from one another. Among the total sixty two Scheduled Tribes of Odisha, there are thirteen Ethno-cultural Primitive Tribal Groups (PTGs). The Lodha tribe is one of the Primitive Tribal Groups of Odisha in Eastern India. The social life style of Lodhas is an interest of the current study. For this reason, this study assess the various social life of Lodhas of Mayurbhanj in Odisha. Methodologically, both primary and secondary sources are used to assess the social way of Lodhas society. Lodhas have its own rules of economic practice that determines its people to define intra-ethnic and inter-ethnic interaction. Lodha tribe pursuit common goals and express their cultural identity and distinctiveness in their social organization, language, rituals, dress, ornaments, art and craft. Thus, the social activities of Lodhas include clanship, family, birth and death rituals, settlement, building their house, marriage system, literacy, education, food habits, social customs, dress and ornaments, work participation, dance, songs, and others.